2022
DOI: 10.1007/s43545-022-00509-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond tokenism and objectivity: theoretical reflections on a transformative equity, diversity, and inclusion agenda for higher education in Canada

Abstract: Universities, the sites for objective knowledge, apolitical and legitimized to contribute to human and intellectual capacity, find themselves in a tenuous position on issues of merit, equality, and fairness. On one hand, social forces have demonstrated how universities have been institutions for the production and reproduction of systemic inequality. On the other hand, universities maintain that they are well positioned, as part of their institutional renewal practices, to address contemporary calls for Equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Inclusion, which emphasizes the need to create environments where individuals feel valued, respected, and supported, was later added to the concept of EDI [ 6 ]. Together, these principles form a framework for creating a more equitable, diverse, and inclusive society, where individuals are not only recognized for their differences but also given equal opportunities to thrive [ 7 , 8 ]. Although the origins of EDI are rooted in the United States, the principles have since been adopted by many organizations and institutions worldwide as a means of promoting social justice and equity [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion, which emphasizes the need to create environments where individuals feel valued, respected, and supported, was later added to the concept of EDI [ 6 ]. Together, these principles form a framework for creating a more equitable, diverse, and inclusive society, where individuals are not only recognized for their differences but also given equal opportunities to thrive [ 7 , 8 ]. Although the origins of EDI are rooted in the United States, the principles have since been adopted by many organizations and institutions worldwide as a means of promoting social justice and equity [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another separate research study on Canadian Universities purported solutions to transformative DEI initiatives undeviating from the strategies we described. The work of Mugo and Puplampu (2022) concluded that to circumvent inequities in hiring and retaining women and racial and ethnic minorities, investing in trainings on consciousness-raising, cultural competency and introspection is paramount to the discourse along with institutional accountability to measure discrete outcomes of candidate hires and faculty promotions (Mugo and Puplampu, 2022). These researchers also endorsed value statements in academic institutions that reflect DEI language and to include this language in strategic planning efforts-all of which provides various ways to socialize DEI concepts among faculty.…”
mentioning
confidence: 99%